2003
DOI: 10.1002/hipo.10113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hippocampal cholinergic deafferentation on learning strategy selection in a visible platform version of the water maze

Abstract: Recent evidence has suggested that the relative levels of acetylcholine (ACh) between brain structures may be an important factor in the choice of behavioral strategy in settings in which either hippocampal or dorsal striatal brain systems can be employed both effectively and independently (McIntyre and Gold. 1999. Soc Neurosci Abs 25:1388). The current investigation used the neurotoxin 192 IgG-saporin to deplete the hippocampus of ACh selectively, while leaving ACh in other brain regions, including dorsal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
(76 reference statements)
3
26
0
1
Order By: Relevance
“…In contrast, all of the 23-mo-old mice swam to the visible platform without visiting the original platform location. Not surprisingly, as in adult rats, most mice in the current study adapted to the new visible platform location by the second strategy probe trial (Devan and White 1999;Bizon et al 2003).…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, all of the 23-mo-old mice swam to the visible platform without visiting the original platform location. Not surprisingly, as in adult rats, most mice in the current study adapted to the new visible platform location by the second strategy probe trial (Devan and White 1999;Bizon et al 2003).…”
Section: Discussionmentioning
confidence: 58%
“…However, this study was carried out 48 hours post surgery at a time when the cholinergic lesion is not complete. More recent studies have found an increased preference for a spatial strategy in rats with MS/VDB lesions (Bizon et al, 2003;Jonasson et al, 2004).…”
Section: -Igg Saporin Lesionsmentioning
confidence: 95%
“…However, this study was carried out 48 hours post surgery at a time when the cholinergic lesion is not complete. More recent studies have found an increased preference for a spatial strategy in rats with MS/VDB lesions (Bizon et al, 2003;Jonasson et al, 2004).The effects of IgG SAP lesions on non-spatial memory tasks have not been as extensively studied, but a few studies have reported no effect on freezing behaviour during fear conditioning to tone or to context following a selective MS/VDB lesion or a complete CBF lesion (Frick et al, 2004). Attentional processes are also affected following a NB lesion as tested on the 5-choice serial reaction task (Lehmann et al, 2003;Harati et al, 2008).…”
mentioning
confidence: 97%
“…Colombo and Gallagher (1998) reported that increases in acetylcholynetransferase activity in the dorsolateral striatum are negatively correlated with the accuracy in hippocampaldependent working memory tasks. Furthermore, alterations in the cholinergic septohippocampal system leading to enhanced or impaired cholinergic function in the hippocampus seem, respectively, to enhance or reduce learning and memory in this structure (Ragozzino and Gold 1995, Janis et al 1998, Gold 2003 (but see Cahill and Baxter 2001, Bizon et al 2003). Simultaneous measurement of acetylcholine in the hippocampus and the striatum showed a correlation between the changes of ACh release and the expression of place response or S-R behaviour Gold 2003b, McIntyre et al 2003).…”
Section: Studying Interactions Between Systemsmentioning
confidence: 98%
“…Additionally, the interactions between the different systems have been studied by testing the facilitating effect of lesioning a system that is not related to the task to be solved (Packard et al 1989, Schroeder et al 2002, Chang and Gold 2003a. Another interesting line of research studies the correlation of neurochemical factors with the expression of different kinds of response (Ragozzino and Gold 1995, Colombo and Gallagher 1998, Janis et al 1998, Bizon et al 2003, Chang and Gold 2003b, McIntyre et al 2003, Marriott and Korol 2003. Devan and White (1999) applied an experimental procedure in which cue and place responses were developed simultaneously in the water maze (figure 1).…”
Section: Experimental Approaches Dissociating Parallel Navigation Sysmentioning
confidence: 99%